The socio-economic impacts of the floriculture industries on the smallholders in Ethiopia: the case of Sululta District in Oromia National Regional State - Kassa, Alemnesh Tsehay; Keno, Gutema Imana; Makahamadze, Tompson; Bekele, Demissie (Frontiers in Horticulture, 2025)
Floriculture industries produce non-edible agricultural products for the global market. Whereas, the smallholder farmers produce edible agricultural products for domestic consumption and they contribute to national food security. The purpose of this article is to uncover the impact of the floriculture industry on the socioeconomic sustainability of the smallholder farmers and associated conflicts in Sululta district, Oromia Regional State in Ethiopia. A qualitative research approach and grounded theory research design were used to carry out the study. Data was collected using document analysis, non-participant observation, and interviews conducted with twenty five research participants, 2 FGDs, and 3 key informants from the local elders. The major findings of the study indicated that floriculture industries have controlled lands in various forms that affect the smallholder farmers’ access to land and water resources. The study highlights the socioeconomic non-sustainability of smallholder farmers in the study area due to social insecurity, agricultural product damage, arable land and water resource access restrictions, resulting in the smallholder farmers shift to daily laborers. The article recommends that the government should balance the foreign exchange earnings from the floriculture industries with the sustainability of the smallholder farmers. The article also recommends government in Ethiopia should promote participatory resource management environmental and social impact assessments to mitigate potential negative impacts of industries on the smallholder farmers’ socioeconomic sustainability.